Study on protective performance of impact-resistant polyurea and its coated concrete under impact loading. (18th July 2022) - Guo, Hui; Du, Cheng; Chen, Yu; Li, Dan; Hu, Wenjun; Lv, Xiao
Highlights: Different proportions of polyurea were designed and their properties were compared. The impact-resistant polyurea coating material was obtained through analysis. Influence of polyurea coating on strength and peak strain of concrete was analyzed. Failure modes of concrete and polyurea-coated concrete under impact were discussed. Energy dissipation law of polyurea-coated concrete under impact load was studied. Abstract: In order to effectively improve the impact resistance of concrete, polyurea elastomer coating with excellent impact resistance is obtained through formula design and performance testing, and it is coated on the end face of concrete specimen to prepare the polyurea-coated concrete composite specimen. The dynamic mechanical properties of the composite specimens are tested by using a large-diameter split Hopkinson pressure bar device. The variation laws of mechanical properties of polyurea-coated concrete under different strain rates and the influence of polyurea coating position on its dynamic properties and failure modes are analyzed, and the energy dissipation performance of polyurea-coated concrete is further discussed. The results shows that both concrete and polyurea-coated concrete exhibit obvious strain rate effects, that is, as the strain rate increases, the failure strength increases, and the fragments increase. When the strain rate is similar, the damage degree of concrete specimen coated with polyurea on front face (load-receiving face) is the lowest and the protection effect is the best. When polyurea is coated on the end face of concrete specimens, the peak strain is significantly increased and the brittleness is improved. With the increase of impact velocity, the peak value of dissipated energy of the composite specimens increases correspondingly, and its energy dissipation coefficient reaches the peak at about 0.45, which shows that as the incident energy peak increases, the dissipated energy peak does not increase indefinitely.